1993
DOI: 10.1111/j.1600-051x.1993.tb00338.x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study on insulin‐dependent diabetes mellitus and periodontal disease

Abstract: In the present two-year longitudinal investigation, the progression of periodontal disease was assessed after 1 year from the baseline examination in 38 dentate subjects and after 2 years in 22 dentate subjects with a mean duration of 18 years of insulin-dependent diabetes mellitus. The diabetics, aged 35 to 56 years at baseline, were under medical treatment at the outpatient clinic of the III Department of Medicine, University Central Hospital of Helsinki and at 2 diabetic clinics of the Helsinki Health Centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
131
1
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(143 citation statements)
references
References 19 publications
3
131
1
4
Order By: Relevance
“…Causes for periodontal diseases are known to be various factors, dental occurrence of periodontal disease is higher and accelerates resorption of alveolar bone, and inadequate control of blood sugar level was related to the severity of periodontal diseases [13][14][15][16][17][18][19][20][21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…Causes for periodontal diseases are known to be various factors, dental occurrence of periodontal disease is higher and accelerates resorption of alveolar bone, and inadequate control of blood sugar level was related to the severity of periodontal diseases [13][14][15][16][17][18][19][20][21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] Individuals with DM tend to have a higher prevalence of periodontal diseases and more severe and rapidly progressing forms than those who do not have DM. 41,48 DM is a known risk factor for periodontitis in adults.…”
Section: Risk Factor Influence On Periodontitis In Type 1 Dmmentioning
confidence: 99%
“…41,48 DM is a known risk factor for periodontitis in adults. Seppälä et al 49 demonstrated that patients with type 1 DM exhibit a higher degree of attachment loss and bone loss than control subjects under similar dental plaque conditions. This finding was confirmed in a follow-up site-by-site study by the same authors.…”
Section: Risk Factor Influence On Periodontitis In Type 1 Dmmentioning
confidence: 99%
“…Metabolic control of diabetes is considered to play the major role in determining the level of periodontal disease. Poorly controlled diabetic patients have more gingival inflammation, periodontal pockets and/or attachment loss than well-controlled diabetic patients (Ervasti et al 1984, Tervonen & Knuuttila 1986, Safkan-Seppälä & Ainamo 1992, Seppälä et al 1993, Tervonen & Oliver 1993, Seppälä & Ainamo 1994. But there are also studies in which no relation between periodontal disease and metabolic control is found (Bacic et al 1988, Hayden & Buckley 1989, Bridges et al 1996.…”
Section: Periodontal Diseasesmentioning
confidence: 99%